Effects of Administration of Fertirelin Acetate and Gentamycin Sulphate after Artificial Insemination on Pregnancy Rate of Cows - Yildiz, Atilla (My University, 2001)
Two studies were conducted to evaluate if Fertirelin acetate (an analogue of GnRH) and Gentamycin sulphate would improve pregnancy rate in healthy cows or in nonpregnant cows although they were inseminated three times or more. The first investigation was carried out in sixty-eight healthy cows. Cows were alloted randomly to one of two treatment groups or one of two control groups when found to be in oestrus. The first treatment group was treated with 100 micrograms of Fertirelin acetate, while the first control grup was given saline (2 ml) intramuscularly immediately after artificial insemination. The second treatment group was treated with 500 mg of Gentamycin sulphate in 50 ml of saline, while the first control group was given saline (50 ml) by intrauterine infusion one hour after Al. The second investigation was carried out in sixty-eight nonpregnant cows although they were inseminated three times or more. Cows were alloted randomly to one of four treatment groups when found to be in oestrus: 1) intramuscular injection with 100 micrograms of fertirelin acetate immediately after artificial insemination; 2) intrauterine infusion with 500 mg of gentamycin sulphate in 50 ml of saline 24 hours after Al: 3) a combination of both therapies; and 4) untreated controls. Animals were observed for repeat oestrus, and pregnancy diagnoses were made by rectal palpation 60 days after Al. In the first investigation, the pregnancy rates were 47 and 41.2 per cent for the first treatment and control groups. Of the second treatment group, 70.6% became pregnant, whereas 537% of the second control group were diagnosed as pregnant. In the second investigation, their conception rates after the first artificial insemination were 35, 70, 75 and 25%, respectively. In conclusion, this study supports the general use of Gentamycin sulphate after Al as a method for enhancing pregnancy rates of cows.
İneklerin Gebelik Oranlari Üzerine Sun'i Tohumlamadan Sonra Uygulanan Fertirelin Asetat ve Gentamisin Sülfat'in Etkisi
Keywords: Cow; Fertirelin acetate; Gentamycin and pregnancy rate